2022
DOI: 10.1002/anie.202203837
|View full text |Cite
|
Sign up to set email alerts
|

From Copper to Basic Copper Carbonate: A Reversible Conversion Cathode in Aqueous Anion Batteries

Abstract: Dual-ion batteries that use anions and cations as charge carriers represent a promising energy-storage technology. However, an uncharted area is to explore transition metals as electrodes to host carbonate in conversion reactions. Here we report the reversible conversion reaction from copper to Cu 2 CO 3 (OH) 2 , where the copper electrode comprising K 2 CO 3 and KOH solid is self-sufficient with anion-charge carriers. This electrode dissociates and associates K + ions during battery charge and discharge. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, the efficacy of the copper electrode decayed rapidly within the alkaline electrolyte [178]. Ji et al [73] reported that the Cu electrode can reversibly store CO 3 2− and OH − anions. In its initial cycle, the Cu electrode exhibited a reversible capacity of 412 mAh g −1 at a current rate of 0.5 A g −1 (Figure 16a).…”
Section: Conversion-type Cathodesmentioning
confidence: 99%
“…However, the efficacy of the copper electrode decayed rapidly within the alkaline electrolyte [178]. Ji et al [73] reported that the Cu electrode can reversibly store CO 3 2− and OH − anions. In its initial cycle, the Cu electrode exhibited a reversible capacity of 412 mAh g −1 at a current rate of 0.5 A g −1 (Figure 16a).…”
Section: Conversion-type Cathodesmentioning
confidence: 99%
“…Galvanic effect is an electrochemical corrosion phenomenon when two metals with different redox potentials contact each other, which could accelerate the etching of anode metal and continuous dissociation of metal ions. , Moreover, galvanic corrosion has been applied across various fields, such as electrochemical hydrogen production, antitumor gas therapy, energy storage, , power generation, , and wastewater treatment . By virtue of the advantage of the galvanic effect, the polymer brushes in SI-Fe 0 ATRP can be further elongated when an Fe(0) plate is employed as an anode material because the dissociation of Fe ions is enhanced by the galvanic effect. , On the other hand, there’s flexibility in choosing cathode materials, such as Au, Ag, and Pt. , Compared to our previously reported galvanic-replacement-assisted SI-Cu 0 ATRP (gr-SI-Cu 0 ATRP) employing nanostructured Cu to enhance the dissociation of Cu ions, the galvanic cell only requires a small amount of inert nanoparticles to decorate the Fe plate, which allows constant access to highly reactive Fe ions. , Moreover, iron galvanic cells are simple and inexpensive to fabricate, especially in precisely customized polymer brushes due to their efficient catalytic effect. ,, …”
Section: Introductionmentioning
confidence: 99%
“…35,36 Galvanic effect is an electrochemical corrosion phenomenon when two metals with different redox potentials contact each other, which could accelerate the etching of anode metal and continuous dissociation of metal ions. 37,38 Moreover, galvanic corrosion has been applied across various fields, such as electrochemical hydrogen production, 39 antitumor gas therapy, 40 energy storage, 41,42 power generation, 43,44 and wastewater treatment. 45 By virtue of the advantage of the galvanic effect, the polymer brushes in SI-Fe 0 ATRP can be further elongated when an Fe(0) plate is employed as an anode material because the dissociation of Fe ions is enhanced by the galvanic effect.…”
Section: Introductionmentioning
confidence: 99%
“…We aim to build a rechargeable voltaic battery from simple and cheap materials, which avoids using expensive, toxic, or corrosive components. As it is known, there is a pH trade-off between the Cu cathode and Zn anode, where Cu prefers an alkaline condition for conversion reactions, , whereas Zn favors a near-neutral solution for plating reactions . Along this line of thinking, if we can create a “locally alkaline” condition from a near-neutral solution, the pH demands of Cu and Zn should be satisfied simultaneously.…”
Section: Introductionmentioning
confidence: 99%